1999
DOI: 10.1002/1529-0131(199904)42:4<780::aid-anr23>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii pneumonia in patients with connective tissue diseases: The role of hospital experience in diagnosis and mortality

Abstract: Objective. Pneumonia due to Pneumocystis carinii has been increasingly reported in patients with connective tissue diseases, but the frequency of this complication is not known. We sought to determine the frequency of P carinii pneumonia (PCP) in patients with connective tissue diseases, and to determine the role that a hospital's acquired immunodeficiency syndrome (AIDS)-related experience may have in the diagnosis of PCP in these patients.Methods. We used a state hospitalization registry to identify all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 18 publications
(26 reference statements)
2
52
1
7
Order By: Relevance
“…The estimated mortality from PCP in patients with underlying connective tissue disease varies according to the underlying disorder; 63% in WG, 58% in inflammatory myopathy, 48% in Polyarteritis Nodosa, 31% in RA and 17% in systemic sclerosis. 7 The overall mortality from PCP in HIV-negative patients is reported to be 30-60%, significantly higher than the reported 10-20% mortality rate in HIV-positive patients. 1,26 Given the higher mortality in HIV-negative patients it has been suggested that the threshold for commencing PCP chemoprophylaxis should be lower in this group of patients.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The estimated mortality from PCP in patients with underlying connective tissue disease varies according to the underlying disorder; 63% in WG, 58% in inflammatory myopathy, 48% in Polyarteritis Nodosa, 31% in RA and 17% in systemic sclerosis. 7 The overall mortality from PCP in HIV-negative patients is reported to be 30-60%, significantly higher than the reported 10-20% mortality rate in HIV-positive patients. 1,26 Given the higher mortality in HIV-negative patients it has been suggested that the threshold for commencing PCP chemoprophylaxis should be lower in this group of patients.…”
Section: Discussionmentioning
confidence: 85%
“…Whereas there are several reports of PCP occurring in patients with rheumatic diseases, the absolute incidence has not been well defined. [5][6][7] In general the risk of PCP appears to be higher in patients with WG as compared with other rheumatic disorders. In a large hospital-based study in California, which examined the incidence of PCP in rheumatology patients over a 12-year period, there were 223 cases of PCP in patients with connective tissue disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A number of studies have described the risk factors, clinical manifestations and outcomes of PCP in patients without HIV infection. [2][3][4][5][6][7][8][9][10][11][12][13] In HIV-negative patients, PCP tends to follow a more acute course, and the mortality rate for patients with PCP has been reported to be 19.6-52.9%, 2,5,7,8, [10][11][12][13] which is considerably higher than the reported mortality among HIV-infected patients with PCP. 14 Most previous studies have used a variety of staining techniques for the diagnosis of PCP.…”
Section: Introductionmentioning
confidence: 99%